2011
DOI: 10.1007/s00383-011-2925-1
|View full text |Cite
|
Sign up to set email alerts
|

Patch repair is an independent predictor of morbidity and mortality in congenital diaphragmatic hernia

Abstract: Infants requiring PR have significantly higher mortality and suffer greater morbidity than those undergoing NPR. This association is independent of other known predictors of mortality. Identifying prenatal features associated with this high risk group would be of great clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
2
23
1
1
Order By: Relevance
“…Several risk factors that were previously associated with chylothorax were also evaluated. Patch repair, as a marker of defect size, has been linked to worse outcomes, secondary to potential thoracic duct injury [14,15]. However, in this study, patch repair was not an independent predictor of chylothorax.…”
Section: Discussioncontrasting
confidence: 50%
“…Several risk factors that were previously associated with chylothorax were also evaluated. Patch repair, as a marker of defect size, has been linked to worse outcomes, secondary to potential thoracic duct injury [14,15]. However, in this study, patch repair was not an independent predictor of chylothorax.…”
Section: Discussioncontrasting
confidence: 50%
“…The majority of the FETO infants underwent a patch repair compared to the minority of the non-FETO infants, highlighting that the former infants had a larger diaphragmatic defect which likely contributed to their greater morbidity [11,14,15]. A patch repair has been associated with a higher mortality, longer duration of supplementary oxygen and greater need for supplementary oxygen at discharge [2,14]. The FETO group was born significantly more prematurely; indeed, their median gestational age was 34 weeks compared to 38 weeks in the non-FETO group.…”
Section: Discussionmentioning
confidence: 94%
“…This is much higher than what has been observed in fetuses with less severe hypoplasia, based on prenatal measurement of the O/E-LHR 18 . The use of a patch is clinically relevant, as earlier work has shown that it is predictive of morbidity 36 . Fetal intervention increased the risk for preterm delivery, which in itself is a cause of morbidity.…”
Section: Discussionmentioning
confidence: 99%